2022
DOI: 10.1111/ced.15052
|View full text |Cite
|
Sign up to set email alerts
|

Eczematous drug eruption in patients with psoriasis under anti‐interleukin‐17A: does interleukin‐22 play a key role?

Abstract: Summary Background Eczematous drug eruption (EDE) is a spongiotic skin reaction in response to systemic medications. To date, EDE has been described in patients treated with anti‐interleukin (IL)‐17A monoclonal antibodies with a prevalence of 2.2%–12.1%. Aim To describe the clinical and histological features and the skin cytokine milieu in patients with EDE induced by anti‐IL‐17A biologics. Methods This was a prospective study, enrolling patients with psoriasis who developed EDE during treatment with two anti‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 23 publications
(79 reference statements)
1
14
0
Order By: Relevance
“…7 Studies have demonstrated that eczematous drug eruption (EDE) is a reactive spongiotic skin reaction to systemic medication, with a prevalence of 2.2-12.1% in patients with psoriasis treated with anti-IL-17A biologics, and that EDE is the result of an imbalance in the Th2/Th22 response secondary to blockade of IL-17A activity. 11 Likewise, scaling and 1660 burning sensations may be rare and paradoxical reactions to biologic therapy in the case of AD treated with dupilumab. Interestingly, the patient's psoriatic lesions showed no recurrence throughout the treatment period.…”
Section: Discussionmentioning
confidence: 99%
“…7 Studies have demonstrated that eczematous drug eruption (EDE) is a reactive spongiotic skin reaction to systemic medication, with a prevalence of 2.2-12.1% in patients with psoriasis treated with anti-IL-17A biologics, and that EDE is the result of an imbalance in the Th2/Th22 response secondary to blockade of IL-17A activity. 11 Likewise, scaling and 1660 burning sensations may be rare and paradoxical reactions to biologic therapy in the case of AD treated with dupilumab. Interestingly, the patient's psoriatic lesions showed no recurrence throughout the treatment period.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of PN was con rmed based on clinical characteristics, laboratory tests, histopathology, and history of medications. Adverse reactions such as atopic dermatitis (AD) [10], eczematous drug eruption [11], and perianal dermatomycosis [12] have been reported in the previous literature during the treatment of psoriasis with IL-17A inhibitors. However, these cases have not been reported in PN.…”
Section: Discussionmentioning
confidence: 99%
“…The Th1 and Th2 pathways are closely related in the immune response, and when the Th1 response is blocked or diminished, the Th2 response is conversely increased, as is antisense [14]. For example, AD during treatment of psoriasis in one case receiving the IL-17A inhibitors [10] and in a prospective study of 289 psoriasis patients treated with ixekizumab and secukinumab demonstrated eczematous drug eruption in 2.8% of patients [11]. The cause was suggested to be the imbalance of Th2/Th22 response to anti-IL-17A drugs by blocking the Th1/Th17 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Fania reported that three psoriasis patients developed psoriasiform skin lesions with augmented expression of IL-22 after receiving adalimumab ( 249 ). Megna also discovered increased levels of IL-22 in psoriasis patients who switched to eczematous drug eruption after treatment of anti-IL-17 biologics ( 250 ). Thus, combined therapies of anti-TNF-α (or anti-IL-23/IL-17) and anti-IL-22 intervention might be effective in anti-TNF-α (or anti-IL-23/IL-17)-resistant psoriasis individuals.…”
Section: Biologics Targeting Il-22 Signaling Pathways In Skin Diseasesmentioning
confidence: 99%